2020
DOI: 10.1038/s41598-020-59639-3
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Injury Induces Postoperative Cognitive Dysfunction

Abstract: Postoperative cognitive dysfunction (POCD) is a major complication affecting patients of any age undergoing surgery. This syndrome impacts everyday life up to months after hospital discharge, and its pathophysiology still remains unclear. Translational research focusing on POCD is based on a wide variety of rodent models, such as the murine tibial fracture, whose severity can limit mouse locomotion and proper behavioral assessment. Besides, influence of skeletal muscle injury, a lesion encountered in a wide ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
7
1
1
Order By: Relevance
“…This is consistent with a recent report that showed that freeze coagulation-induced muscle injury was responsible for inducing PND. 18 However, skeletal muscle loss alone did not affect cognitive function in rats; this is inconsistent with a previous study that showed that athletes with musculoskeletal injuries had some degree of cognitive impairment. 23 The difference in study designs and cognitive tests used might have led to these inconsistent results.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…This is consistent with a recent report that showed that freeze coagulation-induced muscle injury was responsible for inducing PND. 18 However, skeletal muscle loss alone did not affect cognitive function in rats; this is inconsistent with a previous study that showed that athletes with musculoskeletal injuries had some degree of cognitive impairment. 23 The difference in study designs and cognitive tests used might have led to these inconsistent results.…”
Section: Discussioncontrasting
confidence: 77%
“…15,16 Despite these observations, the relationship between sarcopenia and PND is unknown, 17 except 1 report that showed that muscle injury would induce PND. 18 These imply that BDNF secretion might be associated with low skeletal muscle mass due to its relationship with PND. Muscle atrophy can be induced by hind limb unloading, which has been used as an animal model for sarcopenia research.…”
mentioning
confidence: 99%
“…By working on both neurotransmitters and inflammation in CNS, VLX may open a new road to explore the treatment options. Although multiple factors may predispose POCD, only aging is identified as an important one so far ( 50 ). Therefore, we admitted the limitations of the present study such as the young age of mice, which was not the best scenario for mimicking the patients clinically since POCD occurs more often in the elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we admitted the limitations of the present study such as the young age of mice, which was not the best scenario for mimicking the patients clinically since POCD occurs more often in the elderly patients. However, young mice are more suitable for further cellular and molecular mechanism study ( 3 , 50 , 51 ). Old mice were usually used to compare the age effects on the mice response ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research also revealed that sevoflurane also led to the postoperative cognitive dysfunction of human neuronal cells [ 26 ]. Some studies revealed that the occurrence and development of anesthetics induced postoperative cognitive impairment was associated with the inflammation, oxidative stress and apoptosis of cells of central nervous tissues [ 27 , 28 ]. In this study, we also found that stimulation of sevoflurane induced the damage of central nervous tissues.…”
Section: Discussionmentioning
confidence: 99%